ANALYSIS OF ELDERLY SATISFACTION REGARDING ELDERLY POSYANDU SERVICES BASED ON THE FIVE SERVQUAL DIMENSIONS - Heri Triwibowo (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Elderly satisfaction is one of the important indicators in assessing the quality of health services, including services at elderly posyandu (integrated health post for the elderly). Parasuraman's SERVQUAL theory is used as an approach to measure service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study aims to analyze the level of satisfaction among elderly patients regarding the services provided at the Elderly Posyandu in Gembongan Hamlet, Jotangan Village, Mojosari, Mojokerto. The research method employed a quantitative descriptive design with a cross-sectional approach. The sample consisted of 60 elderly respondents selected by total sampling. Data collection was conducted using a structured questionnaire based on the SERVQUAL dimensions. Data analysis was presented in the form of frequency distribution and percentages.The results showed that overall, 51 elderly individuals (85%) expressed satisfaction, 7 elderly individuals (11.7%) expressed very high satisfaction, and 2 elderly individuals (3.3%) expressed moderate satisfaction with the Elderly Posyandu services. No respondents reported dissatisfaction or very high dissatisfaction.The conclusion is that the overall level of elderly satisfaction with the Elderly Posyandu services in Gembongan Hamlet falls within the satisfied category. This achievement reflects a strong synergy among community health volunteers (cadres), primary healthcare center (Puskesmas) health workers, and village government support. Continuous improvement in empathic communication skills and cadre competencies is necessary to optimize service quality, particularly in the dimensions of empathy and assurance